Exploring consumers' attitudes and behaviours toward online hotel room reservations - Kok, Adeline Li Ming *; Teoh, Boon Wai (Scientific & Academic Publishing, 2013)
Marketers in Malaysia need to have solid understanding on consumers’ online attitude and buying behavior. This is mainly due to the shift and trend that consumers are moving fast into online purchasing. Malaysia is rank one of the ten countries in the world with the highest number of internet users. The travel market in the Asia Pacific region is fast growing and more consumers are reserving their hotel reservations via online travel agencies. Hence, the main purpose of this conceptual paper is to explore the factors that influence consumers’ attitude and purchase behaviour toward online hotel room reservations. Four factors which are information, trust, price and convenience have been identified in this study. The focus of this study will be on consumers who reserve their hotel rooms via online travel agents. The research plans to adopt a survey method using stratified random sampling and the hypotheses will be tested using structural equation modelling.